Healthy behaviors according to the perception of health in university students - Riveros-Soto, Iveth (2024)
Background: Non-communicable diseases are responsible for more than 80% of deaths, and in Peru they account for 73% of deaths (World Health Organization, 2022). Objective: to describe the association between the dimensions of health behaviors and health perception in first-year students of a public university in Metropolitan Lima, who reported having some health problem. Method: 285 students aged between 18 and 28 years (M=19.6, SD=1.66) were evaluated and anonymously administered the Health Behavior Questionnaire (CEVJU) by Salazar et al., 2010, and a sociodemographic form designed by the author. Results: showed that students presented correlation between the dimensions of physical activity and sport, recreation and free time management, eating habits and sleep and rest organization, with a good perception of health. A difference was also found between male and female groups, in which males perceive their health better. Conclusions: the students perceived a good state of health, possibly due to adequate health behaviors.